TRADERS, BROKERS AND MARCHERS: THE EASTERN MARKET OF MANAGUA AS A SPACE FOR SOCIAL INTERACTION - Solís Narváez, Norling (Universidad Nacional Autónoma de Nicaragua, Managua. UNAN-Managua, 2014)
The oriental market of Managua is a complex interspace, wherein coexist modernity and tradition, country style and capitalism. The key to understand this small city within a city, by analyzing this complex network social relationships that characterizes it.Analyzing this relationship between them and their customers, it can be seen peculiar mechanisms of interchange and reciprocation that belong of traditional indigenous markets.The ethnographic views allowed immerse in the economic market surface, to take notice in what few observed, what is not recorded about merchant`s life, those who are the market protagonists that energizes the physics space, giving a new meaning to this social interaction environment.Keywords: Social relationships, kinship relations, culture, economy